KONSEP DAN STRATEGI PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM: (Studi Tentang Penerapan Mata Kuliah PAI di Universitas Pasundan Bandung) - Abdul Raup; Maman Maman; Uus Ruswandi; Bambang Samsul Arifin (Bajang Institute, 2023)
The development of world civilization in the era of globalization shows two opposite sides of a coin. On the one hand, the inhabitants of the earth are increasingly spoiled by technological achievements that make it easier for anyone to access information and communicate with anyone in any part of the world. On the other hand, the inhabitants of the earth are increasingly losing their individual identities. Local culture that has wisdom values ​​is increasingly being marginalized, replaced by a hedonic culture, promiscuity, and a culture that is far from polite. Educational institutions are parties that should take a role in overcoming the problems of the community. Higher education as a center of excellence is the hope for a better future. Universities will become institutions that give birth to cadres of national fighters who are ready to be involved in carrying out development agendas. Religious education in tertiary institutions aims to help orderly students who have faith and are devoted to God Almighty, have noble character, think philosophically, be rational and dynamic, have broad views, participate in inter-religious cooperation in the framework of developing and utilizing science and technology and art for human and national interests. Islamic religious education in tertiary institutions is considered capable of tackling student moral degradation such as brawls, drug consumption, alcohol, free sex and so on. The portrait of the implementation of Islamic Religious Education in Higher Education is an interesting object to study. In this case, research was conducted at Pasundan University using research through information sources from online media and directly involved in the research location. The research results are presented with a descriptive analytic pattern.